Answer:
(- 3, - 2 )
Explanation:
Given the 2 equations
- 2x + 5y = - 4 → (1)
3x + 4y = - 17 → (2)
Multiplying (1) by 3 and (2) by 2 and adding the result will eliminate x
- 6x + 15y = - 12 → (3)
6x + 8y = - 34 → (4)
Add (3) and (4) term by term
(- 6x + 6x) + (15y + 8y) = (- 12 - 34), that is
23y = - 46 ( divide both sides by 23 )
y = - 2
Substitute y = - 2 in either of the 2 equations.
Substituting in (2)
3x - 8 = - 17 ( add 8 to both sides )
3x = - 9 ( divide both sides by 3 )
x = - 3
Solution is (- 3, - 2 )